Adaptation and Preliminary Validation of the TRUST for Primary School Teachers (TRUST-PS) - Francesc Sidera; Anna Amadó; Clara Andrés-Roqueta; Ana Górriz Plumed; Georgina Perpiñà; Eloy Soria-Izquierdo; Elisabet Serrat (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
Teachers’ social and emotional competences (SEC) are important both for their well-being and for children’s development. Although there are self-report instruments that assess teachers’ SEC, only the TRUST assesses them directly through challenging secondary school classroom situations that teachers have to respond to. The aim of this research is to adapt it and validate it for primary school teachers, in Catalan language. A total of 143 teachers responded to a sociodemographic questionnaire, to an adaptation of the TRUST for primary school teachers (TRUST-PS), and to an emotional intelligence questionnaire (TEIQue-SF). The results revealed that the TRUST-PS has an adequate internal consistency for their two subtests: emotion regulation (α = .83) and relationship management (α = .87). Also, a two-factor model showed good fit to the data. In conclusion, the TRUST-PS can be used to directly assess primary school teachers’ SEC and be helpful for designing or evaluating teacher trainings.